Development of Direct and Asyncronous Online Learning Models to Improve Student Learning Outcomes During Study From Home the COVID-19 Pandemic - ‪Bachtiar Syaiful Bachri; Andi Mariono; Fajar Arianto (IJORER : International Journal of Recent Educational Research, 2022)
The development of learning needs is increasing as the demand for competency improvement is not only oriented to mastery of the material but also to more complex competencies, namely holistic knowledge, attitudes and skills. At this time the world is being hit by a pandemic due to Covid-19 which hinders direct interaction in learning as usual. So that learning requires the use of communication and information technology (ICT) through learning in the network (online). Through this research, it will be studied to determine the right formula in the selection and use of the synchronous and asynchronous models. This research was conducted using a development research approach with the ADDIE model. conducted at the Educational Technology Study Program, Faculty of Education, State University of Surabaya in the period May – November 2021. The acquisition of learning outcomes in sychronous learning is better than asynchronous. The results of the analysis can be concluded that there is a difference in learning outcomes between the two models, asynchronous and synchronous.